Fundamental maths - Breach, Mark (Basingstoke ; New York : Palgrave Macmillan, 2011)
A short, accessible textbook for students who are entering HE or FE courses and need to re-visit and develop school maths and gain confidence in it. The author explains the maths clearly through words and examples, not just pages of sums, and makes sure students put past anxieties about maths or gaps in their knowledge behind them
Includes index
Keywords: Mathematics